1990
DOI: 10.1051/parasite/1990653151
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania infantumMon-1 isole dePhlebotomus perniciosus, en Kabylie (Algerie)

Abstract: Les progrès accomplis depuis peu en chimiotaxonomie des Leishmania, permettent de déterminer et de classer sans difficulté excessive, les parasites isolés de patients, d'ani maux réservoir ou de vecteurs. Ainsi, grâce à cette tech nique, deux zymodèmes du complexe Leishmania infantum, (1, 2, 3). Au cours de l'été 1988, à l'occasion d'une enquête entomologique en grande Kabylie, nous avons pu isoler une souche appar MON-1 et MON-24, ont été identifiés dans le nord algé rien, chez l'Homme et le Chien

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
8

Year Published

1992
1992
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 2 publications
1
21
0
8
Order By: Relevance
“…P. longicuspis was the second most predominant species (14%) identified in this area, yet this species is mainly found in the semi-arid and the arid bioclimatic zones. During a study conducted in August 1989 in a village (Taourit-Aden, altitude 500 m) located in the vicinity of LNI area, P. perfiliewi, the second predominant species, was found (Izri et al 1990). In our study, P. perfiliewi was poorly represented (<1%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…P. longicuspis was the second most predominant species (14%) identified in this area, yet this species is mainly found in the semi-arid and the arid bioclimatic zones. During a study conducted in August 1989 in a village (Taourit-Aden, altitude 500 m) located in the vicinity of LNI area, P. perfiliewi, the second predominant species, was found (Izri et al 1990). In our study, P. perfiliewi was poorly represented (<1%).…”
Section: Discussionmentioning
confidence: 99%
“…In Algeria, the confirmed vectors are P. perniciosus for L. infantum MON-1 and P. perfiliewi for L. infantum MON-24 (Izri et al 1990;1993). Parrot et al (1941) proposed for the first time P. longicuspis as potential vector of visceral leishmaniasis (VL) parasite, but so far, no confirmatory data have been published.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…P. (L.) perniciosus has got the largest distribution (D = 84 %) (Tables Ia and Ib). It was the most abundant Larroussius species in most studied VL sites (Ghezala, Aïn Jloula and Sidi Salem) and probably represents the main vector of VL in northern and central Tunisia as reported in other Mediterranean countries (Table IIa and IIb) (AlvesPires, 1984;Bettini et al, 1986;Rioux et al, 1986b;Maroli et al, 1988;Izri et al, 1990;Izri et al, 1992). However, in Marthouma, the dominance of P. perniciosus in CDC traps and P. perfiliewi in sticky traps suggests that more than one species could be incriminated in the transmission (Table IIa and IIb) (Dancesco et al, 1970;Alves-Pires, 1984;Rioux et al, 1986b;Izri et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, P. ariasi (Rioux et al 1984a) and P. (L.) perniciosus Newstead 1911 (Izri et al 1990) were demonstrated as vectors of visceral and cutaneous leishmaniases due to Leishmania infantum, both from Portugal to Italy and from Morocco to Tunisia, where Canidae are reservoir hosts. L. infantum may be also present in the semi-arid belt in sympatric condition with L. tropica , and even in the arid belt (Dereure et al 1986).…”
Section: Resultsmentioning
confidence: 99%